DAMPAK CAR FREE DAY TERHADAP PENGHASILAN UMKM KULINER DI KOTA KUPANG: PELUANG DAN TANTANGAN - Sakera, Gabriela; Bulu, Yacobin; Sel, Yohana; Lian, Yohanes (Jurnal Pendidikan dan Ekonomi (JUPEK), 2024)
The impact of Car Free Day (CFD) on the income of culinary Micro, Small and Medium Enterprises (MSMEs) in Kupang City is attracting attention as a local economic phenomenon. CFD offers opportunities for MSMEs to introduce their products to new consumers without significant promotional costs. This research aims to analyze the potential and challenges faced by MSMEs during CFD events. Using descriptive qualitative methods and SWOT analysis, data was collected through interviews with culinary MSME actors. The results show that CFDs increase interaction with consumers and expand the market, although challenges such as weather, limited time and stiff competition remain. MSME players adopt marketing strategies such as special discounts and the use of social media to attract customers. These findings emphasize the importance of government and community support in optimizing the benefits of CFDs for MSME growth.